THE ROLE OF ART IN SOCIO-CULTURAL STRATIFICATION OF SOCIETY - Никоненко, Т. М.; Калініченко, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with topical issues of relations of society and the arts. Disclosed the relationship and cooperation of each other such concepts as a picture of the world, art, subculture, the stratification of society.